Ring-substituted 8-hydroxyquinoline-2-carboxanilides as photosystem II inhibitors - Jampilek, Josef; Kralova, Katarina; Pesko, Matus; Kos, Jiri (Bioorganic & medicinal chemistry letters, 2016)
Ring-substituted 8-hydroxyquinoline-2-carboxanilides inhibited photosynthetic electron transport (PET) through photosystem (PS) II. Their inhibitory efficiency depended on the compound lipophilicity, the electronic properties of the substituent R and the position of the substituent R on the benzene ring. The most effective inhibitors showing IC50 values in the range 2.3-3.6μM were substituted in C'(3) by F, CH3, Cl and Br. The dependence of the PET-inhibiting activity on the lipophilicity of the compounds was quasi-parabolic for 3-substituted derivatives, while for C'(2) ones a slight increase and for C'(4) derivatives a sharp decrease of the activity were observed with increasing lipophilicity. In addition, the dependence of PET-inhibiting activity on electronic Hammett's σ parameter of the substituent R was observed with optimum σ value 0.06 for C'(4) and 0.34 for C'(3) substituted derivatives, while the value of σ parameter did not significantly influence the PET-inhibiting activity of C'(2) substituted compounds. Interactions of the studied compounds with chlorophyll a and aromatic amino acids present in the pigment-protein complexes mainly in PS II were documented by fluorescence spectroscopy. The section between P680 and plastoquinone QB occurring on the acceptor side of PS II can be suggested as the site of action of the compounds.
Keywords: oxychinolin; vazba proteinů; Structure-Activity Relationship; Photosynthesis; Chloroplasts; Photosystem II Protein Complex; fotosyntéza; transport elektronů; Spinacia oleracea; fluorescenční spektrometrie; fotosystém II (proteinový komplex); chlorofyl; chloroplasty; vztahy mezi strukturou a aktivitou; Oxyquinoline; Spectrometry, Fluorescence; Chlorophyll; Anilides; Protein Binding; Electron Transport; anilidy